The Effect of Experiential Marketing and Paylater Features on Customer Satisfaction and Repeat Interest - Dhandy Dwi Yustica (Green Publisher Indonesia, 2021)
This study aims to determine whether experiential marketing and PayLater features on the Gojek application have on consumer satisfaction and their impact on repurchase interest. The data analysis technique uses path analysis and uses quantitative methods. Quantitative methods include validity and reliability, classic assumption tests, t-test trials, F tests, and the coefficient of determination (R2). The number of samples used in this study were 100 respondents. The results of the study indicate that experiential marketing has a significant positive effect on customer satisfaction, the PayLater feature also has a positive effect on customer satisfaction, and the two independent variables simultaneously have a positive effect on customer satisfaction. The findings also show that experiential marketing has a positive effect on repurchase interest, consumer satisfaction has a positive effect on repurchase interest, and different results are shown by the PayLater feature which has a negative effect on repurchase interest. Simultaneously, experiential marketing variables, PayLater features, and customer satisfaction have a positive effect on repurchase interest.